2015
DOI: 10.1186/s40780-015-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the exposure by cyclophosphamide oral tablet

Abstract: BackgroundUnintended exposure to antitumor agents from an oral medicine may place healthcare workers and patients taking medicine at risk. In this study, the exposure to blister pack by CP (cyclophosphamide) and appropriate preventive procedures were examined.FindingsCP detected inside the blister pack of the tested seven lots by LC-MS/MS ranged from 8.2 to 199.6 ng. Raman imaging clearly showed that CP ingredient was completely covered by the tablet coating layer and had not leached out of the tablet. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Exposure to oral HD can occur through contact with contaminated packaging, compounding, counting and repackaging medications, opening capsules, splitting tablets, handling or accidental breaking of capsules or tablets during administration, disposal of contaminated waste, and contact with objects touched with contaminated Personal Protective Equipment (PPE) . In veterinary medicine, risk of exposure during administration may be increased with patients unwilling to consume the drug or resistant to oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to oral HD can occur through contact with contaminated packaging, compounding, counting and repackaging medications, opening capsules, splitting tablets, handling or accidental breaking of capsules or tablets during administration, disposal of contaminated waste, and contact with objects touched with contaminated Personal Protective Equipment (PPE) . In veterinary medicine, risk of exposure during administration may be increased with patients unwilling to consume the drug or resistant to oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…For oral HDs, such as cyclophosphamide or 5-fluorouracil tablets, the risk of exposure to HDs was evaluated by analysing the amount of drugs on the surfaces of the blister packages, and the amount of HDs that may be inadvertently ingested by caregivers during drug administration using feeding tubes 10–12. In a study of injectable anticancer drugs, Böhlandt et al reported that drugs were dispersed via sweat, saliva, and excrement in the homes of patients treated with anticancer drugs 13.…”
Section: Introductionmentioning
confidence: 99%
“…Капсулированные и покрытые оболочкой препараты представляют меньший риск, однако в случае нарушения оболочки капсулы или разрушения таблетки высока вероятность загрязнения рабочих поверхностей препаратом и поступления его в больничную среду. Цитостатиками может быть за-грязнена наружная поверхность флакона (например, от 0,5 нг до 2,4 мкг на флакон 5-фторурацила), внут-ренняя поверхность упаковки-блистера, при вскрытии которого препарат поступает в зону дыхания работни-ка [6,11,12].…”
unclassified